Configuration and Location of Small Urban Gardens Affect Colonization by Monarch Butterflies - Baker, Adam M.; Potter, Daniel A. (Frontiers in Ecology and Evolution, 2019)
Ecological theory predicts that specialist insect herbivores are more likely to locate and colonize host plants growing in relatively sparse or pure stands compared to host plants growing amongst diverse non-host vegetation. We tested the hypothesis that increasing the apparency and accessibility of milkweed (Asclepias spp.) host plants in small polyculture gardens would boost their colonization by the monarch butterfly (Danaus plexippus), an iconic native species of conservation concern. We established replicated gardens containing the identical mix of milkweeds, flowering nectar sources, and non-host ornamental grasses but arranged in three different spatial configurations that were monitored for monarch colonization over two successive growing seasons. Monarch eggs and larvae were 2–3 times more abundant in gardens having milkweeds evenly spaced in a 1-m corridor around the perimeter, surrounding the nectar plants and grasses, than in gardens in which milkweeds were surrounded by or intermixed with the other plants. Predator populations were similar in all garden designs. In a corollary open-field experiment, female monarchs laid significantly more eggs on milkweed plants that were fully accessible than on milkweeds surrounded by non-host grasses of equal height. In addition, we monitored monarch usage of 22 citizen-planted gardens containing milkweed and nectar plants in relation to their botanical composition, layout, and surrounding hardscape. Multivariate analysis explained 71% of the variation, with significantly more eggs and larvae found in gardens having milkweeds spatially isolated as opposed to closely intermixed with non-host plants, and in gardens having 100 m north/south access unimpeded by structures. Numerous programs encourage citizens to establish gardens with milkweed and nectar plants to help offset habitat loss across the monarch's breeding range. Our findings suggest guidelines for garden design that can help make the urban sector's contributions to monarch habitat restoration more rewarding for participants, and of greater potential value to monarch recovery.